Multiscale Fracture of Ti-Al-N Coatings under Uniaxial Tension; Physical Mesomechanics; Vol. 24, iss. 2 - Shugurov A. R. Artur Rubinovich; Panin A. V. Alexey Viktorovich; Dmitriev A. I. Andrey Ivanovich; Nikonov A. Yu. Anton Yurjevich (2021, 2021)
Title screen